Clinical significance of serum β2-Microglobulin determination in neoplastic disease of adults and children - Balcerska, Anna; Bień, Ewa (Contemporary Oncology/Współczesna Onkologia, 2003)
β2-Microglobulin (β2-M) is a low molecular weight protein that constitutes the light chain of the class I major histocompatibility complex (MHC). It is present on the cell surface of most nucleated cells (mainly lymphocytes T, B and macrophages) and the membrane turnover is the principal source of β2-M in blood and body fluids. It has been widely used as a nephrological and immunological diagnostic tool. Its significance as a tumour marker helpful in diagnostics and neoplasms’ activity assessment has not been defined yet. Elevated serum levels of β2-M have been stated in adult patients with several types of lymphoproliferative disorders, such as multiple myeloma, non-Hodgkin’s and Hodgkin’s lymphomas, B-cell chronic lymphocytic leukemia and adult T-cell leukemia. To the contrary, the clinical usefulness of β2-M determination in most malignant solid tumors in adults seems to be rather limited. The paper presents up-to-date knowledge concerning the structure, biological function and significance of serum β2-Microglobulin estimation in different malignant disorders. The diagnostic, prognostic and monitoring role of β2-M determination among oncological patients has been analysed. Since there have been no reports considering the role of serum β2-M in children with cancer, we have discussed the results of our own studies on clinical significance of β2-microglobulin in diagnostics and treatment monitoring in children suffering from neoplastic disease.